Booster Pump Performance Analysis Towards Rotation Of Impeller For CSD Dredger Type - Tony Bambang Musriyadi; Siti Faridhah Raudhatun Naifah (International Journal of Marine Engineering Innovation and Research, 2017)
Dredger are a vessel for lift materials from sub surface to another place above the water surface. Dredger divided into some types such Suction Dredger, Bucket Dredger, Backhoe Dredger, and Water Injection Dredger. Cutter Suction Dredger is equipped with a rotating cutter head, for cutting and fragmenting hard soils. The soil is sucked up by means of dredge pumps, and discharged through a floating pipeline and pipes on shore, to a deposit area. In some cases, the material is discharged into split hopper barges that are moored alongside the Cutter Suction Dredger. These split hopper barges unload the soil at the deposit area. The most important part of dredger are the pump unit, NPSH is needed to figure the pump performance ability and how the efficiency number of the pump. Booster pump performance analysist are needed to mantain the pump's performance and efficiency. This thesis are describe about drawing process and computerized simulation at Ansys Software for pump performance with 3 different fluid types and 5 variations of impeller rotation. The number of NPSHa are 6.8 m and 2.8 for the NPSHr. Based on the pure water state, the lowest RPM value of 300 was obtained with V = 1.1366 m / s and Q = 1227.52 m3 / h, the highest RPM value of 600 with the result v = 1.1259 m / s and Q = 1215.97 m3 / h. Then the pumps used in this final project are more efficiently used for fluid types which tend to be condensed from the liquid, and less efficient for use in the state of pure water fluid